2008
DOI: 10.1002/gepi.20310
|View full text |Cite
|
Sign up to set email alerts
|

A multiple testing correction method for genetic association studies using correlated single nucleotide polymorphisms

Abstract: Multiple testing is a challenging issue in genetic association studies using large numbers of single nucleotide polymorphism (SNP) markers, many of which exhibit linkage disequilibrium (LD). Failure to adjust for multiple testing appropriately may produce excessive false positives or overlook true positive signals. The Bonferroni method of adjusting for multiple comparisons is easy to compute, but is well known to be conservative in the presence of LD. On the other hand, permutation-based corrections can corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
731
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 700 publications
(737 citation statements)
references
References 35 publications
4
731
0
2
Order By: Relevance
“…For approximation methods, we choose SimpleM (Gao et al 2008) to represent the approaches of estimating the number of independent tests, and SLIDE (Han et al 2009) to represent the approaches using the MVN framework. These two methods have been shown to be superior to other alternatives within their classes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For approximation methods, we choose SimpleM (Gao et al 2008) to represent the approaches of estimating the number of independent tests, and SLIDE (Han et al 2009) to represent the approaches using the MVN framework. These two methods have been shown to be superior to other alternatives within their classes.…”
Section: Resultsmentioning
confidence: 99%
“…One approach is to estimate the effective number of independent tests from the eigenvalues of the correlation matrix of the SNPs (Cheverud 2001;Nyholt 2004;Li and Ji 2005;Gao et al 2008;Moskvina and Schmidt 2008;Pe'er et al 2008). Previous studies have shown that these methods may yield inaccurate results (Salyakina et al 2005;Han et al 2009).…”
mentioning
confidence: 99%
“…8 They found that extreme tail theory produced a more accurate estimate for M eff while still being computationally efficient. Cheverud and Nyholt's method is known to be overly conservative, 3,4 and Moskvina and Schmidt did not compare extreme tail theory with some of the more recent M eff methods as we do here. Thus, the relative merits of extreme tail theory versus more recently proposed M eff methods remain untested.…”
Section: Introductionmentioning
confidence: 87%
“…Gao et al's method estimates the M eff as the number of eigenvalues needed to explain a prespecified proportion of the sum of all of the eigenvalues. 3 They suggest that a threshold of 0.995 works well in most situations, although a higher or lower threshold would likely perform better depending on the LD structure of the gene region. We use Gao's recommendation of c ¼ 0.995 in our implementation.…”
Section: And Ji 4 M Li and Jimentioning
confidence: 99%
See 1 more Smart Citation